Land Use Conversion and Soil Properties in a Lowland Tropical Landscape of Papua New Guinea - George, Nangu; Killur, Rajashekhar Rao Bangadi; Cornelio, David Lopez (Jurnal Manajemen Hutan Tropika, 2013)
Land use conversion affects natural soil processes and can potentially decrease soils productivity.  A representative area was selected to study the effects of land use conversion in Unitech Campus, Southeastern lowlands of Papua New Guinea (PNG).  Area selected for the study was once covered by tropical rainforest and has been subjected to various  land  use  types  over  time.    Representative  soil  samples were  collected  under  4 main  land  use  types (secondary forest, plantation forest, grassland, and agricultural garden) at 2 depths (0-0.15 m and 0.15-0.30 m) with 3 replicates per land use.   Soil bulk density, water infiltration rate, and cumulative water infiltration values were significantly greater (p < 0.05) under grasslands than under secondary and plantation forests. Among soil chemical properties, extractable potassium content and pH showed significant differences (p < 0.05) among the land uses, pH values increased upon conversion of forested lands to grassland or agricultural gardens. Conversion of  secondary  forests  into grasslands or agricultural gardens  leads  to depletion of Bray's phosphorus and extractable potassium.   Tree-based land uses were optimum due to better nutrient cycling conditions and lower bulk density compared  to grassland and agricultural garden despite  the  low pH conditions and  lower water  infiltration.